2015
DOI: 10.1155/2015/316719
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Recycled Porous Hot Mix Asphalt with Gilsonite Additive

Abstract: The objective of the study is to evaluate the performance of porous asphalt using waste recycled concrete material and explore the effect of adding Gilsonite to the mixture. As many as 90 Marshall specimens were prepared with varied asphalt content, percentage of Gilsonite as an additive, and proportioned recycled and virgin coarse aggregate. The test includes permeability capability and Marshall characteristics. The results showed that recycled concrete materials seem to have a potential use as aggregate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Djakfar et al [25] evaluated the performance of porous asphalt mixtures using recycled concrete and investigated the impact of gilsonite addition to the mixture. The results showed that using gilsonite at ranges of 8-10% (the optimum content was 9%) increased the Marshall characteristics of the mixture, especially its stability without lessening the permeability capability of the porous asphalt mixtures.…”
Section: Asphalt Modified With Gilsonite As a Sole Modifiermentioning
confidence: 99%
See 1 more Smart Citation
“…Djakfar et al [25] evaluated the performance of porous asphalt mixtures using recycled concrete and investigated the impact of gilsonite addition to the mixture. The results showed that using gilsonite at ranges of 8-10% (the optimum content was 9%) increased the Marshall characteristics of the mixture, especially its stability without lessening the permeability capability of the porous asphalt mixtures.…”
Section: Asphalt Modified With Gilsonite As a Sole Modifiermentioning
confidence: 99%
“…Regarding Marshall tests, the use of gilsonite in asphalt mixtures can improve the Marshall properties of mixtures by increasing Marshall stability [24,27,30,38,42]. Moreover, the stability value continued to increase when the rate of gilsonite increased up to 10% [25,27], enhancing the resistance against deformation of the asphalt mixture [24].…”
Section: Critical Evaluation Of Gilsonite As Asphalt Modifiermentioning
confidence: 99%
“…The Marshall quotient was determined for each specimen, as the ratio between Marshall stability and Marshall flow. Despite having already been discussed as partial representativity of the Marshall results with regard to the bituminous mixtures' response [91][92][93][94], such a test is currently used due to the huge experience gained all around the world.…”
Section: Hot MIX Asphalts (Hmas)mentioning
confidence: 99%
“…Furthermore, the Marshall quotient has been computed per each specimen, equal to the ratio between Marshall stability and Marshall flow. Even if it has been previously outlined the partial representativity of the Marshall data with respect to the asphalt concrete behaviour, such a test is still widely adopted given the large experience Advances in Civil Engineering cumulated over the years [38][39][40][41]. Table 5 gives additional details concerning the correspondence between specimens and gradations shown in Figure 2.…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%